Concomitant medication use and its implications on the hazard pattern in pharmacoepidemiological studies: example of antidepressants, benzodiazepines and fracture risk - Marie Louise De Bruin (Epidemiology, Biostatistics and Public Health)
Background: Antidepressants and benzodiazepines are often co-prescribed and both associated with an increased fracture risk, albeit with distinctive hazard patterns. Timing of initiation of one with respect to the other and duration of use may influence the combined fracture hazard. The objective of our study was to describe patterns of concomitant use of benzodiazepine and antidepressants in terms of timing of initiation and duration and to illustrate the potential impact of various scenarios of timing of co-use on hip fracture hazard.   Methods: Patients initiating antidepressant therapy (2002-2009) were identified from the Netherlands Primary Care Research Database. Concomitant benzodiazepine use was assessed according to the start time of benzodiazepine with respect to antidepressant therapy start. Duration of concomitant use was estimated relative to the length of antidepressant treatment episode.   Results: Among 16,087 incident antidepressant users, 39.0% used benzodiazepines concomitantly during their first antidepressant treatment episode. The time of initiation of benzodiazepine use was variable (64.4% starting before, 13.7% simultaneous and 21.9% after antidepressants). Duration of concomitant use in the three groups varied.   Conclusions: Co-prescribed medications with a common adverse event, may not only require accounting for concomitant use, but also the timing of start and duration of use as the overall hazard may vary accordingly.